The Effect of Smart Engklek Game on the Motor Development of 4-5 Years Old Children - Adiyanti, Nita; Jannah, Miftachul; Yulianty, Nadya (International Conference on Islamic Studies, 2022)
Motor development is a process of maturity that a person has since birth as a form of skill to move his body that involves both gross and fine motor skills to achieve a goal. The purpose of this study was to determine the effect of the engklek game on the development of children aged 4-5 years through the smart engklek game. The method used is a quantitative approach to Quasi Experiment Design. Based on the results of calculations through independent t-test, the experimental class t-test value = 8.509 and with df = 58. The t-table value at t is 0.05 = 2.704 with a significant value (P) = 0.000 > = 0.05. With Thus the value of t count > t table which means HO is rejected and H1 is accepted. While the calculation of the control class is obtained by the value of t-test = 8,509 with df = 58 the price of t table at t 0.05 = 2.704 with significant (P) = 0.001 > = 0.05 seen that the value of t count > t table means Ho rejected and H1 accepted. Thus, the smart engklek game provides a significant influence on children's motor development.